The phenomenon of religious dispute as missionary activity (on the example of Kharkiv province at the beginning of the XX centure). - Pototsky, Viacheslav (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2023)
Purpose. The purpose of the article is to highlight the process of expanding the practice of conducting religious disputes in the Kharkov province at the beginning of the 20th century. Public discussions between Orthodox missionaries and representatives of local sectarianism and Old Believers are considered as one of the forms of complex interfaith relationships in the region. Research methodology. The methodological basis of the article are the principles of historicism and objectivity, implemented by general logical methods (analysis and synthesis), as well as classification, comparative, and periodization methods. Scientific novelty. For the first time in domestic historiography the intellectual component of the practical activity of functionaries of the internal mission of the Russian Orthodox Church in a certain diocese became the subject of a special scientific study. On the basis of missionary reports, as well as reports of secular publicists and messages from sectarians, the role of the organizers of these disputes was considered, the range of issues under consideration was outlined, and the peculiarities of the behavior of the participants were analyzed. Conclusions. At the beginning of the 20th century, the inter-confessional situation in the Kharkiv province noticeably worsened. There were numerous cases of disrespect for Orthodox priests, blasphemy and even violence committed by sectarians of various directions. The same way, representatives of the religious majority very often resorted to aggressive behavior. New missionaries I. Aivazov and D. Bogolyubov tried to return from the confrontation to the competition of ideas. It is they who took the initiative to conduct public debates between representatives of the official church and adherents of other religious movements. This became especially relevant after the laws of 1905-1906 declaring freedom of conscience in the Russian Empire. The new practice quickly aroused sincere interest and won the sympathy of a wide range of residents of the Kharkiv province. These meetings usually attracted many spectators, were covered in the press, and discussed on the streets. However, the main drawback of such debates was the subjectivity of the perception of their results by the representatives of the opposing sides, when in the absence of clear criteria for victory, everyone could attribute success in the contest.